Between Equity and Empathy: Social Professions and the New Accountability - Sarah Banks (Social Work and Society, 2007)
This article explores the practical and ethical implications of the "˜new accountability' (working to procedures, targets and standards) based on interviews with British social professionals. Although similar tendencies are present in other European countries, in Britain the rule-bound nature of social work is more intense. Practitioners who regard the "˜new accountability' positively justify their views with reference to utilitarian and rights-based arguments relating to the promotion of good outcomes, the achievement of equity, respecting the consumer rights of service users and the rights of other stakeholders to information and value for money. Those practitioners who view the new accountability requirements negatively seem to speak in a different 'moral voice', which can be linked to more personal and situated approaches to ethics, stressing the importance of particular relationships in context, trust, sensitivity and a sense of 'vocation'. Both 'voices' are part of professional practice, but the new accountability stresses the former at the expense of the latter. For social work to play the critical role identified by Walter Lorenz, maintaining a creative balance between equity and empathy will be important.